Repeatability of thermal reaction norms for spontaneous locomotor activity in juvenile newts - Baškiera, Senka; Gvoždík, Lumír (Journal of thermal biology, 2019)
Locomotor activity is a major attribute of animals. Although this trait determines important ecological processes, such as dispersal and species interactions, the sources of its variation are not fully understood. We examined the influence of body temperature (13, 18, 23, and 28 °C) and individual identity on spontaneous locomotor activity in juvenile alpine newts, Ichthyosaura alpestris, over three consecutive weeks. Locomotor activity was characterized by four parameters: distance covered, mean velocity, frequency of movements, and total activity rate (all directional and non-directional movements). Apart from total activity rate, thermal reaction norms for locomotor parameters had convex or concave curvilinear shapes. During the first trial series, i.e. across the four body temperatures that were tested, individual identity explained less variation in thermal reaction norms than during the second series. Individual means, i.e. the vertical positions of individual thermal reaction norms, were repeatable between trial series in all locomotor activity parameters but the frequency of movements. We conclude that spontaneous locomotor activity is a complex trait, which can be characterized by several parameters with varying individual repeatability and thermal dependency. This information should be considered for planning further locomotor activity experiments, conservation strategies, and modeling ectotherm responses to climate change.
Keywords: Animals; Temperature; Salamandridae; lokomoce; zvířata; tělesná teplota; Body Temperature; teplota; Locomotion